Revisiting the welfare state paradox: A firm-level analysis from Japan. (February 2017) - Mun, Eunmi; Brinton, Mary C.
Highlights: Analyzing data from over 1000 large Japanese companies from 1987 to 2009, we find that employers have tended to promote more, not fewer, women subsequent to policy changes. Employers promote more women into managerial jobs when they actually do provide such benefits. The weakness of the external labor market in Japan reshapes employers characterization of work-family policies from a cost to an opportunity. Abstract: Many cross-national studies of welfare states and gender inequality report adverse effects of work-family policies on women's labor market outcomes. Countries with generous work-family policies tend to have a lower proportion of women in positions of authority and greater occupational sex segregation than countries without such policies. In order to explain this paradox, scholars have argued that work-family policies may create incentives for employers to exclude women from well-paying jobs. This argument, however, has been left untested due to the absence of firm-level data on promotions. This paper seeks to make both a theoretical and an empirical contribution to this literature. At the theoretical level, we argue that the effect of work-family policies is contingent upon labor market context and organizational practices, which shape employers' incentives or disincentives to implement work-family policies to more fully utilize female workers. Empirically, we use over-time firm-level data to test how government policy interventions in Japan to increase work-family benefits have affected female promotion rates in private companies. Analyzing changes in women's promotion rates across 1000 large companies from 1987 to 2009, we find evidence that employers have tended to promote more, not fewer, women subsequent to policy interventions. Additionally, employers who provided more generous work-family benefits promoted more women. Our findings point to the importance of labor market context in structuring employers' incentives to leverage work-family policy reforms to utilize skilled female labor.